2023
DOI: 10.3389/fneph.2023.1105676
|View full text |Cite
|
Sign up to set email alerts
|

Lupus nephropathy beyond immunosuppression: Searching for nephro and cardioprotection

Abstract: Renal involvement in systemic lupus erythematosus (SLE) represents one of the most frequent organ manifestations, often leading to end-stage kidney disease (ESKD). Several therapies have been tested in patients with lupus nephritis (LN) to prevent further organ damage. The effectiveness of immunosuppressive therapy as a treatment for LN is abundant, supported by multiple clinical trials that have shown its efficacy in preventing the development of chronic kidney disease (CKD). In addition to immunosuppressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Kidney function in all these patients remained stable. Similarly, Morales reported the use of empagliflozin in five patients with lupus nephritis resulting in a mean decrease in proteinuria from 2.2 to 1.2 g per day [41 ▪ ]. Observation extended to two months only.…”
Section: What Are the Data On The Use Of Sodium-glucose Cotransporter...mentioning
confidence: 83%
“…Kidney function in all these patients remained stable. Similarly, Morales reported the use of empagliflozin in five patients with lupus nephritis resulting in a mean decrease in proteinuria from 2.2 to 1.2 g per day [41 ▪ ]. Observation extended to two months only.…”
Section: What Are the Data On The Use Of Sodium-glucose Cotransporter...mentioning
confidence: 83%
“…SLE is a multisystemic disease, with hematological, skin, heart, lung, kidney, joint, and cerebral involvement and with a complex pathogenicity, intensively studied in previous decades [ 6 , 8 , 15 ]. The present study evaluated the inflammatory profile orchestrated by inducible nitric oxide synthase in systemic lupus erythematosus and lupus nephritis, showing that renal lesions could be a consequence of inflammation-associated hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation, oxidative imbalance, immune activation, autoantibody production, overstimulation of type 1 interferon (IFN), generation of inflammatory mediators, and tissue damage are fundamental contributors to SLE pathogenesis [ 1 , 2 , 3 ]. A series of experimental data have suggested that reactions mediated by inducible synthase of nitric oxide (NOS2 or iNOS) could be involved in the pathogenesis of SLE [ 4 , 5 , 6 , 7 , 8 ]. An inflammatory stimulus triggers iNOS production, further orchestrating inflammation, angiogenesis, and tissue fibrosis [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations